Merawat Hidup Bersama Di Tengah Kemajemukan dan Konflik Antarumat Beragama - Prasetio L. Th Matitaputty (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2021)
Wayame is one of the villages that did not get involved in the social conflict in 1999. This does not mean that Wayame village does not care about other villages because it does not participate in conflicts. However, in Wayame village, it is true that the conflict only brings destruction in the social ties of the community which in turn can have a traumatic impact on the pluralistic Wayame community. Wayame Village, which is not involved in the conflict and looks harmonious - is not as easy as one might imagine. The existence of a harmonious life process in the midst of diversity in Wayame village has hard efforts made by village governments, religious leaders, and especially people who have a love for Wayame village. Efforts and work to maintain harmony in Wayame village require the involvement of all elements of society, therefore Wayame village formed a TEAM 20 consisting of 10 Christians and 10 Muslims to maintain the stability of the village and the community so as not to get involved in the conflict at that time. In efforts to maintain harmony in the midst of a pluralistic society, it is necessary to understand the religions that exist in society, therefore the theology of religions is necessary to find a common goal as religious human beings in the midst of diversity.